2020
DOI: 10.3390/agronomy10081066
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effect of Petroleum-Derived Substances and Their Bioremediation on the Host Plant (Vicia faba L.) and a Herbivore (Sitona spp.)

Abstract: The present study assessed distant-in-time effects of soil contamination with petroleum-derived substances (PDSs) (petrol, diesel fuel and used engine oil) and their bioremediation using ZB-01 biopreparation on the growth of broad bean, content of nutrients and heavy metals in plants, and feeding by imagines and larvae of Sitona spp. The results showed that even after 5 years from the moment of soil contamination by engine oil and diesel fuel, they negatively impacted the growth of broad bean plants. PDSs sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The biostimulation of degradation by the addition of wastewater sludge in this type of pollution was found to be ineffective [47]. In our experiment, however, biopreparation ZB-01 caused decrease in C 12 -C 36 hydrocarbon content by 470 mg kg −1 and 80 mg kg −1 in fourth-and fifth-year post contamination, respectively [6,37].…”
Section: Hydrocarbons Degradationcontrasting
confidence: 48%
See 3 more Smart Citations
“…The biostimulation of degradation by the addition of wastewater sludge in this type of pollution was found to be ineffective [47]. In our experiment, however, biopreparation ZB-01 caused decrease in C 12 -C 36 hydrocarbon content by 470 mg kg −1 and 80 mg kg −1 in fourth-and fifth-year post contamination, respectively [6,37].…”
Section: Hydrocarbons Degradationcontrasting
confidence: 48%
“…C 12 -C 36 levels in P-contaminated soil were 12 mg kg −1 in P 0R and 7 mg kg −1 in P R [6]. In 2015, C 12 -C 36 hydrocarbon levels in the sections contaminated with oils were still higher than those in the control samples, but these levels had decreased by approximately 40% compared to those in the previous year [37]. The analysis of soil pH in 2014 revealed that the PDSs caused an increase in soil acidification, which was particularly evident for EO-contaminated soil, in which the pH value in H 2 O was nearly 1 scale lower than that in the initial soil (6.01 and 7.12 for EO 0R and initial soil, respectively).…”
Section: Selected Soil Parameters: Hydrocarbon Content Ph and C Total...mentioning
confidence: 89%
See 2 more Smart Citations
“…A positive correlation between soil contamination with petrol and the content of zinc, iron, and manganese in alfalfa plants leaves was also demonstrated by Martí et al [ 61 ]. Gospodarek et al [ 62 ], who tested the effect of a dose 6 g of petrol per 1 kg −1 d.m. of soil, observed reduced accumulation of copper, lead, zinc, nickel, iron, and manganese in aerial parts of Vicia faba beans.…”
Section: Discussionmentioning
confidence: 99%